The Impact of Carbonated Soft Drink Comsumption on Oncular Health-A Review - Shah, Sushant Kumar; Priya Patnaik; Yashwanth BA (Gayaku Publisher, 2024)
Carbonated soft drinks (CSDs), widely consumed globally, have been linked to numerous health issues such as obesity, diabetes, and including ocular complications. The composition of these beverages, including high sugar content and additives, contributes to oxidative stress in ocular tissues. Elevated glucose levels from excessive sugar intake may damage the ocular surface’s glycocalyx, weakening and increasing susceptibility to infections. CSDs also contribute to obesity and type 2 diabetes, both of which are risk factors for significant eye diseases like glaucoma, age-related macular degeneration, and cataracts. While occasional consumption of CSDs may not have severe consequences, excessive intake poses long-term risks for both systemic and ocular health. The review calls for increased awareness about these potential risks, emphasizing the need for further research specifically targeting the direct effects of CSDs on the eyes. Public health campaigns should consider incorporating information on the ocular impacts of sugary drink consumption alongside well-known risks to general health, thereby encouraging healthier lifestyle choices to protect vision